Estado del arte trabajo infantil. (2012)
The present article is a result of the first phase of the investigation titled ‘The Magdalena needs happy children’, in which the state of the art that is going to be investigated about the population of the minors that study and work in the district of Santa Marta and the Magdalena is shown.